Creative economy, cultural economics and entrepreneurship – Questions for a masters programme in its adolescence. An Interview with Mariangela Lavanga and Ellen Loots. (May 2019) - Vickery, Jonathan; Lavanga, Mariangela; Loots, Ellen
The purpose of this interview is to discuss the aims, objectives and achievements of a pioneering European masters degree – in the context of the politics of higher education and the economics of the creative industries.